Overactive bladder (OAB) and its association with prostatic parameters - Tan, W.S.; Low, W.Y.; Ng, C.J.; Khoo, E.M.; Ho, E.L.M.; Tan, H.M. (2011)
Background: Overactive bladder (OAB) is an idiopathic condition characterized by urgency with or without urge incontinence often associated with frequency or nocturia. In this study, we hypothesized that prostatic parameters might be responsible for symptoms seen in OAB patients. Methods: This is a cross-sectional study involving 1007 men >= 40 years old; with a response rate of 53.6. Face-to-face interviews were carried out with semi-structured questionnaires which included socio-demography, self reported medical illness and an OAB questionnaire using a 6-point Likert scale. OAB was defined as 'quite a bit' to 'a very great deal' in either questions: "An uncomfortable urge to urinate", "A sudden urge to urinate with little or no warning", "An uncontrollable urge to urinate" and "Urine loss associated with a strong desire to urinate". Prostatic parameters were assessed using transrectal ultrasound, International Prostate Symptom Score (IPSS) questionnaire, urinalysis and uroflow studies. Results: Results from 537 men with a mean age of 58.2 +/- 8.1 years were analysed. The prevalence of OAB was 16.9 (n = 91). The prevalence of lower urinary tract symptoms or LUTS (IPSS moderate-severe) was 36.1 (n = 195). Men with OAB were significantly more likely to score worse on IPSS (OAB: 30, non-OAB: 4.7, p <= 0.001) (mild-moderate VS severe). Prostate calcification (OAB: 70.3, non-OAB: 58.4, p = 0.035), prostate volume (>= 30cc) (OAB: 35.2, non-OAB: 19.5, p = 0.002), and urine white cell count or WCC (>5WCC/mu L) (OAB: 5.5, non-OAB: 1.3, p = 0.025) were significantly associated with OAB. Multivariate regression analysis revealed that men with severe LUTS (p <= 0.001, OR: 6.7, CI 95: 3.4-13.4) and prostate volume >= 30cc (p = 0.07, OR: 2.0, CI 95: 1.2-3.4) were independently associated with OAB. Conclusions: OAB was significantly associated with prostate calcification, larger prostate volume (>= 30cc) and urinary WCC (>5WCC/mu L). However, only severe LUTS and prostate volume >= 30 cc were independently associated with OAB. (c) 2011 WPMH GmbH. Published by Elsevier Ireland Ltd. All rights reserved.